Refuting the myth of non‐response to exercise training: ‘non‐responders’ do respond to higher dose of training - Montero, David; Lundby, Carsten (The Journal of physiology, 2017)
Key points The prevalence of cardiorespiratory fitness (CRF) non‐response gradually declines in healthy individuals exercising 60, 120, 180, 240 or 300 min per week for 6 weeks. Following a successive identical 6‐week training period but comprising 120 min of additional exercise per week, CRF non‐response is universally abolished. The magnitude of CRF improvement is primarily attributed to changes in haemoglobin mass. The potential for CRF improvement may be present and unveiled with appropriate exercise training stimuli in healthy individuals without exception. One in five adults following physical activity guidelines are reported to not demonstrate any improvement in cardiorespiratory fitness (CRF). Herein, we sought to establish whether CRF non‐response to exercise training is dose‐dependent, using a between‐ and within‐subject study design. Seventy‐eight healthy adults were divided into five groups (1–5) respectively comprising one, two, three, four and five 60 min exercise sessions per week but otherwise following an identical 6‐week endurance training (ET) programme. Non‐response was defined as any change in CRF, determined by maximal incremental exercise power output (Wmax), within the typical error of measurement (±3.96%). Participants classified as non‐responders after the ET intervention completed a successive 6‐week ET period including two additional exercise sessions per week. Maximal oxygen consumption (V̇O2 max ), haematology and muscle biopsies were assessed prior to and after each ET period. After the first ET period, Wmax increased (P < 0.05) in groups 2, 3, 4 and 5, but not 1. In groups 1, 2, 3, 4 and 5, 69%, 40%, 29%, 0% and 0% of individuals, respectively, were non‐responders. After the second ET period, non‐response was eliminated in all individuals. The change in V̇O2 max with exercise training independently determined Wmax response (partial correlation coefficient, rpartial ≥ 0.74, P < 0.001). In turn, total haemoglobin mass was the strongest independent determinant of V̇O2 max (rpartial = 0.49, P < 0.001). In conclusion, individual CRF non‐response to exercise training is abolished by increasing the dose of exercise and primarily a function of haematological adaptations in oxygen‐carrying capacity. Key points The prevalence of cardiorespiratory fitness (CRF) non‐response gradually declines in healthy individuals exercising 60, 120, 180, 240 or 300 min per week for 6 weeks. Following a successive identical 6‐week training period but comprising 120 min of additional exercise per week, CRF non‐response is universally abolished. The magnitude of CRF improvement is primarily attributed to changes in haemoglobin mass. The potential for CRF improvement may be present and unveiled with appropriate exercise training stimuli in healthy individuals without exception.